J. Ahrens e A. Meteling (eds.), Comics and the City: Urban Space in Print, Picture and Sequence (Altre Modernità, 2015)
J. Ahrens e A. Meteling (eds.), Comics and the City: Urban Space in Print, Picture and Sequence